Familial Non-Medullary Thyroid Cancer Represents an Independent Risk Factor for Increased Cancer Aggressiveness: A Retrospective Analysis of 74 Families - Tavarelli, Martina; Russo, Marco; Terranova, Rosy; Scollo, Claudia; Spadaro, Angela; Sapuppo, Giulia; Malandrino, Pasqualino; Masucci, Romilda; Squatrito, Sebastiano; Pellegriti, Gabriella (Frontiers in Endocrinology, 2015)
Objectives To assess whether familial non-medullary thyroid cancer (FNMTC) represents an independent risk factor for increased aggressiveness of the tumor, as concern as the clinical presentation and the long-term follow-up in respect of sporadic differentiated thyroid cancer (SDTC). Design Retrospective study; 1976–2014. Patients and Methods Seventy-four FNMTC families (151 affected individuals): family relationship and number of affected family members were evaluated. Clinical and histopathological features and outcome were compared to that of 643 SDTC patients followed in the same period according to the same institutional protocols. Median follow-up was 57.7 months (range 12–136) in FNMTC and 59.7 (range 15–94.6) in SDTC patients. Results Three cases occurred in 3 families and 2 cases in the other 71. F:M was 3.7:1 in FNMTC and 4.3:1 in SDTC (NS). The family relationship was siblings in 62.2%. Mean age at diagnosis was lower in FNMTC than in SDTC (p < 0.005). Papillary/follicular histotype distribution was similar (86%). Papillary tumors were more frequently multifocal in FNMTC (p = 0.004) and with lymph-node metastases (p = 0.016). Disease-free survival (DFS) was shorter in FNMTC vs. SDTC (p < 0.0001) with 74.8 vs. 90.8% patients free of disease at the last control (p < 0.005). Three patients died in FNMTC group vs. 1 in SDTC (p = 0.02). Conclusion Familial non-medullary thyroid cancer displays distinct characteristics as earlier age of onset and increased aggressiveness at diagnosis and a higher rate of persistent/recurrent disease and mortality with a shorter DFS in respect with SDTC. FNMTC patients, therefore, should be followed accurately. As the specific gene (or genes) responsible for susceptibility for FNMTC has not yet been identified, a low frequency periodic screening of relatives DTC patients may be useful to identify FNMTC patients at early stage of disease.